Mixing Properties of Room Temperature Patch‐Antenna Receivers in a Mid‐Infrared (λ ≈ 9 µm) Heterodyne System. Issue 2 (23rd December 2019) - Bigioli, Azzurra; Gacemi, Djamal; Palaferri, Daniele; Todorov, Yanko; Vasanelli, Angela; Suffit, Stephan; Li, Lianhe; Davies, A. Giles; Linfield, Edmund H.; Kapsalidis, Filippos; Beck, Mattias; Faist, Jérôme; et al.
Abstract: A room‐temperature mid‐infrared (λ = 9 µm) heterodyne system based on high‐performance unipolar optoelectronic devices is presented. The local oscillator (LO) is a quantum cascade laser (QCL), while the receiver is an antenna coupled quantum well infrared photodetector optimized to operate in a microcavity configuration. Measurements of the saturation intensity show that these receivers have a linear response up to very high optical power, an essential feature for heterodyne detection. By providing an accurate passive stabilization of the LO, the heterodyne system reaches at room temperature the record value of noise equivalent power (NEP) of 30 pW at 9 µm and in the GHz frequency range. Finally, it is demonstrated that the injection of microwave signal into the receivers shifts the heterodyne beating over the large bandwidth of the devices. This mixing property is a unique valuable function of these devices for signal treatment in compact QCL‐based systems. Abstract : Progress on 9 µm heterodyne detection employing room temperature patch‐antenna receivers and quantum cascade lasers is reported. The noise equivalent power is in the pW range at 1.7 GHz. The heterodyne receiver also acts as frequency mixer, when injected with microwave bias. This enables the generation of sidebands that shift the heterodyne signal over the whole band pass of the system.